(untitled) (Academic Journal of Internal Affairs, 2018)
In case of a confrontation between requirements of rightfulness and lawfulness in the way of dilemma solution can be considered already as solved in the theoretic approach “due to the prohibition of use indices acquired in a not allowable way, it does not matter how suitable were these for clearing up, legal order has a priority to truth.” In opposite to that in judgment practice this polemics cannot be considered yet as a settled question, as it is to see nowadays first of all in divergent assessment in the use of voice and picture records made under rights violation as an evidence. The practical importance of this problem shows that – according to judgment experiences – participants of crime procedures, independent of their position in the procedure, try to support more and more often their statements by records made without knowledge and assent of the other party.